Pengelolaan Sumber Belajar oleh Guru Pendidikan Agama Islam - Tiya Sulistiyani (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
The importance of learning resources in learning activities cannot be denied anymore. However, learning resources in madrasas and schools generally have not been managed and utilized optimally. The purpose of this study was to determine the management of learning resources by Islamic religious education teachers who focused on textbooks as learning resources at SMP Negeri 1 Tembilahan Hulu. The results of the research through a questionnaire obtained a percentage of 83.33% categorized as